2015
DOI: 10.1063/1.4927798
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Brillouin flow in planar, conventional, and inverted magnetrons

Abstract: The Brillouin flow is the prevalent flow in crossed-field devices. We systematically study its stability in the conventional, planar, and inverted magnetron geometry. To investigate the intrinsic negative mass effect in Brillouin flow, we consider electrostatic modes in a nonrelativistic, smooth bore magnetron. We found that the Brillouin flow in the inverted magnetron is more unstable than that in a planar magnetron, which in turn is more unstable than that in the conventional magnetron. Thus, oscillations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…2.5. Simon [38] has explicitly shown that the smoothbore magnetron was an adequate description for the equilibrium state. Still, two models dominate the literature: a multistream model based on individual cycloidal particle orbits, and the Brillouin model that idealizes the electron motion as a laminar flow [54].…”
Section: Electron Dynamicsmentioning
confidence: 99%
See 3 more Smart Citations
“…2.5. Simon [38] has explicitly shown that the smoothbore magnetron was an adequate description for the equilibrium state. Still, two models dominate the literature: a multistream model based on individual cycloidal particle orbits, and the Brillouin model that idealizes the electron motion as a laminar flow [54].…”
Section: Electron Dynamicsmentioning
confidence: 99%
“…Still, two models dominate the literature: a multistream model based on individual cycloidal particle orbits, and the Brillouin model that idealizes the electron motion as a laminar flow [54]. Full derivations of the following equations in planar and cylindrical smoothbore magnetrons have been published in many textbooks [6,45,47,54] and theses [10,38,55,56], and will not be repeated here. The following discussion instead focuses on the relevance of the results as they apply to the design of the MFRPM and the interpretation of the experimental results.…”
Section: Electron Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…For a smooth bore magnetron, the negative (positive) mass effect in the inverted (conventional) magnetron geometry was shown to increase (decrease) the severity of the diocotron instability [4] in the Brillouin flow. Including the SWS on the anode, the resonant interaction of the vacuum circuit mode and the corresponding smooth-bore diocotron-like mode is the dominant cause for instability [5].…”
mentioning
confidence: 99%